Changes in household purchasing of soft drinks following the UK soft drinks industry levy by household income and composition: controlled interrupted time series analysis, March 2014 to November 2019 - Jean Adams; Martin White; Stephen J Sharp; Harry Rutter; David Pell; Steven Cummins; Richard D Smith; Nina Trivedy Rogers (BMJ Nutrition, Prevention & Health)
Background The WHO recommends taxes on sugar sweetened beverages (SSBs) to improve population health. We examined changes in volume of and amount of sugar in purchases of soft drinks according to household income and composition, 19 months following the implementation of the UK soft drinks industry levy.Methods Data were from the Kantar Fast Moving Consumer Goods panel, a market research panel which collects data on weekly household purchases (mean weekly number of households=21 908), March 2014–November 2019. Interrupted time series analysis of volume and sugar purchases was used to estimate absolute and relative differences in the volume and amount of sugar in soft drinks, confectionery and alcohol purchased weekly by household income (<£20 000, £20–50 000 or >£50 000) and composition (presence of children (<16 years) in the household (yes or no)), 19 months after soft drinks industry levy (SDIL) implementation, compared with the counterfactual scenario based on pre-announcement trends and using a control group (toiletries).Results By November 2019, purchased weekly sugar in soft drinks fell by 7.46 g (95% CI: 12.05, 2.87) per household but volumes of drinks purchased remained unchanged, compared with the counterfactual. In low-income households, weekly sugar purchased in soft drinks decreased by 14.0% (95% CI: 12.1, 15.9) compared with the counterfactual but in high-income households increased by 3.4% (1.07, 5.75). Among households with children, sugar purchased decreased by 13.7% (12.1, 15.3) but increased in households without children by 5.0% (3.0, 7.0). Low-income households and those with children also reduced their weekly volume of soft drinks purchased by 5.7% (3.7, 7.7) and 8.5% (6.8, 10.2) respectively. There was no evidence of substitution to confectionary or alcohol.Conclusion In the second year following implementation of the SDIL, effects on sugar purchased were greatest in those with the highest pre-SDIL purchasing levels (low-income households and those with children). The SDIL may contribute to reducing dietary inequalities.Trial registration number ISRCTN18042742. Registered: August 2017.